Quanto Interest-Rate Exchange Options in a Cross-Currency Libor Market Model - Hsieh, Tsung-Yu; Chou, Chi-Hsun; Chen, Son-Nan (Asian Economic and Financial Review, 2015)
The purpose of this paper is to price quanto interest-rate exchange options (QIREOs) based on a practical and easy-to-use interest-rate model. According to the payoff structure of QIREOs, the cross-currency LIBOR market model (CLMM), in which the initial LIBOR market model (LMM) is extended from a single-currency economy to a cross-currency economy, is suitable to be adopted to price four different types of quanto interest-rate exchange options in this article. Our pricing formulae represent the general formulae in the framework of the CLMM. Hedging strategies are also provided for practical implementation.